Implementasi Madzhab Teori Belajar Behaviorisrik dalam Proses Pembelajaran Bahasa Arab - Rohmah, Nabilatur; Firdausiyah, Arroyyabah; Bakar, Muhammad Yunus Abu (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2023)
This study aims to explore a knowledge about the Implementation of the School of Behavioral Learning Theory in the Process of Learning Arabic. By doing an analysis of books and scientific journals in order to conclude a good research. In the process of life requires knowledge, as a way to get knowledge that is by learning. In education, there are several types of theories that are used, one of which is the Behaviostic Theory. For this reason, this study uses implementation during learning in order to find out how and can apply it correctly. By exploring the main ideas, characters, developments and trials of Behavioristic theories.